MDT: A simple tool to facilitate dropcasting on in situ TEM MEMS chips - Matthias Quintelier; Joke Hadermann (HardwareX, 2025)
In situ transmission electron microscopy with holders based on the use of micro-electromechanical systems provides valuable insights into material kinetics, yet sample preparation remains complex due to fragile silicon nitride (Si3N4) windows and the risk of leaks and contamination during dropcasting. This results in failed experiments and increases experimental costs. This paper introduces the MEMS Dropcasting Tool (MDT), a cost-effective, in-house 3D-printable solution that confines the droplet to a specific area, preventing particle migration under the O-ring and reducing contamination risks at the inlet and outlet ports of closed cell chip holders.